Sosialisasi Pentingnya Warming-Up Sebelum Melakukan Olahraga Bagi Masyarakat Desa Jayasakti Kecamatan Muaragembong - Fikri, Muhammad Abdul; Aini, Kuratul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam 45 Bekasi, 2024)
The purpose of this community service activity is to explain the important role of WARMING-UP BEFORE DOING EXERCISE FOR THE COMMUNITY. The main purpose of warming-up is to prepare the body for the upcoming physical activity. This helps increase blood flow to the muscles, increases body temperature, and improves flexibility. By warming up, you can reduce your risk of injury and maximize your performance. This activity was carried out on March 10 2023 targeting parents of Al Hidayah KB KB students, activities in this method use training such as socialization. This program ran smoothly and was successfully implemented because parents began to recognize the important role in developing children's creativity.